Business cycles around the globe: a regime switching approach - Sumru Altuğ; Melike Bildirici (TÜSİAD-Koç University Economic Research Forum, 2010)
This paper characterizes business cycle phenomena in a sample of 22 developed and developing economies using a univariate Markov regime switching approach. It examines the efficacy of this approach for detecting business cycle turning points and for identifying distinct economic regimes for each country in question. The paper also provides a comparison of the business cycle turning points implied by this study and those derived in other studies and by other methods. Our findings document the importance of heterogeneity of individual countries' experiences. We also argue that consideration of a large and diverse group of countries provides an alternative perspective on the co-movement of aggregate economic activity worldwide.
Keywords: E32; E37; C32; 330; Markov switching approach; business cycles; turning point analysis; nonparametric modelling; Konjunktur; Konjunktureller Wendepunkt; Nichtparametrisches Verfahren; Welt